(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article artistic heritage Y. Balasaguni interpreted in the context of modern political science. The subject of analysis is the basic idea of «Kutadgu Bilik» the author of the poem ( «KuttyBilik»). Interesting is the author of the writing of this work. Introducing work convinces the reader that the author of the poem Y. Balasagun - outstanding poet and thinker of the largest of all Turks early Middle Ages. In its work, Y. Balasagun great poetic talent and skill describe and solve complex social problems associated with the policy, political power and the state. He is one of the first thinkers who sang an ideal ruler and the state, given the images of different categories of people, and the rulers of the various social strata, representatives of secular and religious power of contemporary society. Key words: state, poem, «Kutadgu bilik» («Kutty bilik»), ideal ruler, thinker, Turks, poet, medieval society, history, politics, tradition.